2012
DOI: 10.5535/arm.2012.36.3.320
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging as a Determinant for Surgical Release of Congenital Muscular Torticollis: Correlation with the Histopathologic Findings

Abstract: Objective (1) To present the magnetic resonance imaging (MRI) findings of congenital muscular torticollis (CMT) of subjects who underwent surgical release and subjects who showed a good prognosis with stretching exercises and (2) to correlate the MRI findings with the histopathologic findings of CMT for subjects who underwent surgical release in order to examine the hypothesis that the MRI findings of CMT can be used as a determinant to perform surgical release of CMT. Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…4 However, approximately 10 to 20 percent of patients with congenital muscular torticollis have a large amount of fibrosis composed of dense connective tissue within the sternocleidomastoid muscle. 5 This subgroup of individuals with congenital muscular torticollis does not respond well to stretching exercises. 5 Therefore, surgical treatment is needed for this subgroup of patients to minimize the secondary musculoskeletal complications of congenital muscular torticollis.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…4 However, approximately 10 to 20 percent of patients with congenital muscular torticollis have a large amount of fibrosis composed of dense connective tissue within the sternocleidomastoid muscle. 5 This subgroup of individuals with congenital muscular torticollis does not respond well to stretching exercises. 5 Therefore, surgical treatment is needed for this subgroup of patients to minimize the secondary musculoskeletal complications of congenital muscular torticollis.…”
mentioning
confidence: 98%
“…5 This subgroup of individuals with congenital muscular torticollis does not respond well to stretching exercises. 5 Therefore, surgical treatment is needed for this subgroup of patients to minimize the secondary musculoskeletal complications of congenital muscular torticollis. 3 The ideal age for surgical treatment of congenital muscular torticollis is younger than 5 years.…”
mentioning
confidence: 98%
“…For establishing the diagnosis of CMT, ultrasonography or MRI has been used to detect the characteristic fibrotic lesion in the SCM [4]. However, in these two case reports, the patients did not show fibrosis or thickening of the SCM.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study MRI findings have been found to be correlated with histopathological findings [19].…”
Section: Diagnosismentioning
confidence: 92%